EFEKTIFITAS KOMPRES EKSTRAK JAHE TERHADAP NYERI SENDI LANSIA DENGAN ARTHRITIS GOUT DI PANTI SOSIAL TRESNA WERDA KHUSNUL KHOTIMAH PEKANBARU - Silvia Nora Anggraini; Novry Fitri Yanti (HEALTH CARE : JURNAL KESEHATAN, 2018)
Compress Ginger Extract is non pharmacological treatment to lower joint pain with a variety of good effects such as stimulating an erection, inhibiting the release of enzyme 5-lipooksigenase and cyclooxygenase and increase endocrine gland activity. The number of elderly who experience joint pain in this way is also effective because the compress ginger extract has many benefits one of them meberi sense of warmth in the joints. This study aims to determine the effectiveness of compress ginger extract on the reduction of joint pain in the elderly of panti sosial tresna werdha khusnul khotimah pekanbaru riau. This research type is quantitative with pre experimental design research, Sampling technique by total sampling, the sample of this study amounted to 39 respondents, the intervention is given once for 3 days with 13 respondents every day. Evaluation by filling in the observation sheet. The result of alternative t test of wilcoxon was found the effectiveness of ginger extract compress on the decrease of aged joint pain with mean before ginger extract was given 6.83 with standard deviation 1,298 and after given compress ginger extract was 4,11 with standard deviation 1,410, p value 0,000 was statistically significant (p <0.05). The results of this study can be a consideration of existing nurses in the hospital and in the community in the reduction of joint pain in the elderly.